Faktor Penentu Tingginnya Minat Muzaki dan Munfik dalam membayar Zakat dan Infak pada Saat Kejadian Luar Biasa - Ohorella, Sakinah; Aan Julia (UNISBA Press, 2025)
Abstract. Zakat and infak play a crucial role in promoting equitable welfare distribution, particularly during extraordinary events (KLB) such as natural disasters or economic crises. This study aims to analyze the factors influencing the interest of muzakki in paying zakat and munfik in giving infak to BAZNAS in Cianjur Regency during such emergencies. The examined factors include knowledge, trust, income, and empathy, which are presumed to significantly influence the willingness of muzakki and munfik in fulfilling their obligations.This research employs a descriptive method with a quantitative approach. Data were collected through Likert-scale-based questionnaires distributed to muzakki and munfik in Cianjur Regency. The results reveal the key factors determining their interest in paying zakat and giving infak during extraordinary events: (1) Knowledge with a score of 478 (Good category), (2) Trust with a score of 486 (Good), (3) Income with a score of 484 (Good), and (4) Empathy with a score of 487 (Very Good). Among these, empathy emerged as the most dominant factor influencing the high interest in zakat and infak during extraordinary events, with a score of 487 in the